Expanded Listening as a way of conducting ethnographic research - Meza-Aguirre, José Alberto; Hernández-González, Edilberto; Montes-Miranda, Alexander Javier (Universidad Pedagógica y Tecnológica de Colombia, 2024)
The aim of this article is to describe a methodology called Escucha Expandida (expanded listening hereinafter) as a way of conducting ethnographic research. This proposal stems from the field work of a doctoral dissertation in progress, which relates artisanal fishing and its roots to the territory in the village of la Boquilla, located in Cartagena de Indias, Colombia. In the methodology section, three moments are outlined: i) the researcher's listening in the research setting, ii) the relational listening of the bodies, iii) the reflexivity. Fishers who carry out artisanal seine fishing in the territory participate in the research, this being the only criterion of inclusion of the people linked to the study.  The research concludes that ethnographic expanded listening generates a condition of relationality understood as a possibility of listening to ourselves in the midst of a living and non-living space -territory-.